PENGARUH INVENTORY INTENSITY, KEBIJAKAN UTANG DAN PERTUMBUHAN PENJUALAN TERHADAP TAX AVOIDANCE - Muhammad Rizal Saragih; Rusdi Rusdi; Andri Sjahputra (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to test and provide empirical evidence of the effect of inventory intensity, debt policy and sales growth on tax avoidance in food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) in 2016-2021. This type of research is quantitative research and uses secondary data in the form of annual financial reports obtained from the official website of the Indonesia Stock Exchange (IDX). The population in this study were 38 companies in the food and beverage subsector that were listed on the Indonesia Stock Exchange (IDX) in 2016-2021. The sampling technique used purposive sampling method and obtained as many as 12 sample companies with a period of 6 years so that the data analyzed amounted to 72 data. The analysis technique used is logistic regression with the help of the eviews 12 program. The results show that simultaneously inventory intensity, debt policy, sales growth have a significant effect on tax avoidance. Meanwhile, partially, inventory intensity has a significant effect on tax avoidance, but debt policy and sales growth have no significant effect on tax avoidance.